Improving investment coordination in electricity networks through smart contracts - Christine Brandstätt; Gert Brunekreeft; Nele Friedrichsen (Jacobs University Bremen, Bremer Energie Institut, 2011)
Smart contracts based on voluntary participation and optionality can be a low transaction cost solution to implement locational signals in distribution networks and thereby avoid network investment. This paper examines the efficiency properties of smart contracts. Based on a three-node example network we show that cases exist in which smart contracts can achieve a pareto-improvement compared to the status-quo even with voluntary participation. With the pareto improvement at least one party is better of under a smart contract without worsening the situation for anyone else. We note that this requirement is very restrictive and leaves significant potential for efficiency improvements by smart contracts untapped. We then discuss the implementation of smart contracts with incentive regulation. There are two main tasks for the regulator: allowing network operators flexibility to offer such contracts and incentivizing network operators to do so.
Keywords: D23; D43; L14; L22; 330; network investment; distribution networks; locational pricing; smart contracts